PREDIKSI KESULITAN KEUANGAN DITINJAU DARI KONEKSI POLITIK DAN KEBERAGAMAN DEWAN - Ratih Dwi Siswani; Shinta Permata Sari (JURNAL ILMIAH EDUNOMIKA, 2024)
Every company strives to maintain its business continuity and avoid bankruptcy. Financial distress are the initial condition of a company experiencing bankruptcy. That condition initiate every company to see factors that can cause financial distress. This research is a type of quantitative research using secondary data, namely the annual report of Consumer Non-Cyclical companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling. The total sample is 57 Consumer Non-Cyclical companies during the period 2020-2022. The regression data analysis methods are used to test hypotheses. The results of this study show that the political connections, board gender diversity, and board national diversity of the council effect the financial distress. However, the board educational diversity and board tenure diversity have no effect on financial distress. Keywords : financial distress, political connections, board educational diversity, board gender diversity, board national diversity, board tenure diversity